Digital distraction in the classroom: exploring instructor perceptions and reactions. Issue 3 (3rd April 2022) - Flanigan, Abraham E.; Babchuk, Wayne A.
ABSTRACT: We examined college instructors' perceptions of student use of mobile technology for off-task purposes during class. Previous research demonstrated that digital distraction hinders student learning, yet little is known about instructor views and reactions to this behavior. Phenomenological interviews with 11 college instructors revealed that student digital distraction has a profound influence on their pedagogical decision-making, relationships with students, and professional satisfaction. These instructors regularly encounter student digital distraction during class and have well-defined views on the deleterious influence digital distraction has on the integrity of the classroom learning environment. However, instructors were divided in their perceived responsibility to curb this behavior. Most rely on proactive prevention strategies rather than reactive strategies out of concern for negatively impacting student-instructor rapport. Moreover, these instructors experience frustration stemming from student digital distraction. Findings indicate that student digital distraction influences pedagogical decision-making and threatens the quality of student-instructor rapport.